045 Delayed-release dimethyl fumarate demonstrated no difference in clinical outcomes versus fingolimod in patients with relapsing-remitting multiple sclerosis: results from the real-world effect study. Issue 6 (24th May 2018) - Sloane, Jacob; Theodore Phillips, J; Calkwood, Jonathan; Walt, Anneke Van der; Min, Jinny; Okwuokenye, Macaulay; Taylor, Catherine
Abstract : Introduction: In real world comparative effectiveness studies of relapsing-remitting multiple sclerosis (RRMS) patients, treatment with delayed-release dimethyl fumarate (DMF) compared with fingolimod (FTY) for ≤2 years was associated with no statistically significant differences in relapse outcomes. We assessed the real-world effectiveness of DMF compared with FTY in RRMS patients at 12 months. Methods: EFFECT (NCT02776072 ) was an observational, international, retrospective, single time point, medical record review study undertaken to evaluate the effectiveness of DMF and other disease-modifying therapies (DMTs). Patient eligibility criteria included age ≥18 years, diagnosis of RRMS, treatment naïve or 1 prior DMT (interferon or glatiramer acetate), DMT treatment initiation after, December 2010 and ≥12 months of medical record data following DMT initiation. Endpoints included Kaplan-Meier estimated proportion of patients relapsed at 12 months and annualised relapse rate (ARR). Substantive baseline covariates were used in estimating propensity score. The data were divided into 4 strata using propensity score. After assessing for balance in baseline covariates between treatment groups, Kaplan-Meier estimates and estimate of treatment effects were pooled across strata of propensity score. Results: Of the 826 DMF and 785 FTY patients enrolled at sites in 17 countries, 816 and 781 patients respectively, were included in the full analysis set. Treatment groups were balanced after propensity score stratification. At 12 months, 86% of DMF-treated patients and 94% of FTY-treated patients remained on therapy. In the trimmed full analysis set, the estimated proportion of DMF patients that relapsed at 12 months was 12% compared with 13% for FTY patients; hazard ratio (95% CI) 1.07 (0.78, 1.46; p=0.6926). At 12 months after treatment initiation, the adjusted ARR ratio (95% CI) was 1.09 (0.80, 1.49; p=0.5754) for patients treated with DMF compared with FTY. Conclusion: Over 12 months, treatment with DMF versus FTY was associated with no statistically significant difference on relapse outcomes.